2015
DOI: 10.3390/ijms161125993
|View full text |Cite
|
Sign up to set email alerts
|

Global Profiling of Various Metabolites in Platycodon grandiflorum by UPLC-QTOF/MS

Abstract: In this study, a method of metabolite profiling based on UPLC-QTOF/MS was developed to analyze Platycodon grandiflorum. In the optimal UPLC, various metabolites, including major platycosides, were separated well in 15 min. The metabolite extraction protocols were also optimized by selecting a solvent for use in the study, the ratio of solvent to sample and sonication time. This method was used to profile two different parts of P. grandiflorum, i.e., the roots of P. grandiflorum (PR) and the stems and leaves of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
(28 reference statements)
0
25
0
Order By: Relevance
“…As reported, 20 components were identified from the root of Korean PG, including oleanolic acid‐type triterpenoid saponins (platycoside G 1 , G 2 , E, D and A, platycodin D 2 , D 3 , D and A and deapioplatycodin D), organic acids (maleic acid, 2‐hydroxyfuran‐3‐formic acid, 2‐furoic acid and citric acid), saccharides (planteose, α ‐kojibiose), amino acid (glutamine), sesterterpenoid (brusatol), alcohol (lobetyolin) and ketone (arnebifuranone).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…As reported, 20 components were identified from the root of Korean PG, including oleanolic acid‐type triterpenoid saponins (platycoside G 1 , G 2 , E, D and A, platycodin D 2 , D 3 , D and A and deapioplatycodin D), organic acids (maleic acid, 2‐hydroxyfuran‐3‐formic acid, 2‐furoic acid and citric acid), saccharides (planteose, α ‐kojibiose), amino acid (glutamine), sesterterpenoid (brusatol), alcohol (lobetyolin) and ketone (arnebifuranone).…”
Section: Resultsmentioning
confidence: 90%
“…The Traditional Medicine Library within UNIFI contains more than 6000 compounds from 600 herbs. In 2015, Lee et al reported the global profiling of various metabolites in PG by UPLC‐QTOF/MS . In this paper, a method based on UPLC‐QTOF/MS in the negative ion mode was developed.…”
Section: Introductionmentioning
confidence: 99%
“…The result demonstrated that most of primary platycosides may be degraded or not absorbed in gastric-intestinal tract, which was in accordance with the previous reports. 20,24 Furthermore, some differences between the metabolites in vitro and in vivo were found. The metabolites of platycosides in vivo all contained glucoses at C-3, but in vitro the glucoses could be easily hydrolyzed by enzyme that produced by intestinal bacteria; the secondary platycosides without saccharide chain at C-28 were the main absorbed compounds in vivo, but the saccharide chain at C-28 cloud not be enzymatic hydrolyzed in vitro and the main metabolites of platycosides in vitro were the compounds with the acetylated saccharide at C-28.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetic studies of platycodin D, platycodin D3 and deapioplatycodin D have shown that these platycosides have low oral bioavailability, which due to the poor permeability and degradation in the gastrointestinal tract. [20][21][22][23][24][25] In that case, we consider that activities of Jiegeng could be caused by the metabolites of platycosides or other absorbed platycosides.…”
Section: Introductionmentioning
confidence: 99%
“…The profiling of active components in herbal medicine with high‐resolution mass spectrometry coupled with gas chromatography (GC) and liquid chromatography (LC) was extensively studied by many researchers in single plants or decoctions made from a mixture of several herbs (Tian et al, ; Chen, Yu, Lu, Lin, & Cheng, ; Ahmad et al, ; Zou et al, ; J.W. Lee, Ji, et al, ; Zhang, Wang, Ma, Zhu, & Wang, ; J. Lee et al, ; S. Guo, Duan, Qian, Tang, et al, ; S. Guo, Duan, Qian, Wang, et al, ; W. Li, Tang, Chen, & Duan, ). Therefore, the present study included profiling, identifying multicomponents using ultra‐high‐performance liquid chromatography quadrupole time‐of‐flight mass spectrometry (UPLC–QTOF–MS) in SCRT and applying multivariate analysis of the metabolomics technique to compare the change in components between the mixture of herb extracts (SCRTM) and decoction of SCRT (SCRTD).…”
Section: Introductionmentioning
confidence: 99%